PENGARUH SUMBER MEDIA PELARUT NUTRISI PADA TEKNOLOGI HIDROPONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Javandira, Cokorda; Putu Lasmi Yuliyanthi Sapanca; Putu Eka Pasmidi Ariati; Yunus Wides Bani (Agrofarm: Jurnal Agroteknologi, 2024)
Brassica rapa L or commonly called mustard pakcoy is one of the most popular types of vegetables in Indonesia, because mustard pakcoy is one of the varieties that contain various health benefits. This study aims to determine "The Influence of Nutrient Soluble Media Sources on Hydroponic Technology on The Growth and Yields of Pakcoy Plants (Brassica rapa L)". The method used was a Randomized Block Design (RAK) with 5 treatments of hydroponic nutrient solvent media. Treatment P1 (30 ltr AC water and 330 ml AB mix), P2 (30 ltr PDAM water and 330 ml AB mix), P3 (30 ltr well water and 330 ml AB mix), P4 (30 ltr irrigation water and 330 ml AB mix and P5 (30 liters of River Water and 330 ml of AB mix).The results showed that treatment P2 (30 liters of PDAM water and 330 ml of AB mix) gave the best growth and yields on the parameters of plant height (cm) and number of leaves (sheet). Meanwhile, the P1 treatment gave the best growth and yield on the parameters of leaf area (cm2), total plant fresh weight (g) and total plant oven dry weight (g).